Developing a Model of Outcome Performance Indicator Web of Water Quantity, Pressure, Continuity and Quality for Accountability Result - Andy Fefta Wijaya (Jurnal Aplikasi Manajemen, 2010)
This research develops a model of Outcome Performance Indicator Web of Water Quantity, Pressure, Continuity and Quality. A qualitative research ia applied for this research. This study identifies multiple indicator relationships requiring a systemic approach in which iterative cycle processes of interconnections among these indicators are evaluated. This exercise of outcome performance measurement is considered as accountability means for evaluating social equity and environmental justice concerns in the three desirable sectors of governance: the government, the enterprise and the society. This is a part of public sector accountability for result.Keywords: Outcame performance, accountability result